Current state of metal melt crystallization theory. Foundry production and metallurgy - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия, 2022)
The classical theory of crystallization of metal melts has been investigated. It is shown that it does not correspond to the second law of thermodynamics. Based on thermodynamic analysis, it was found that the classical theory of crystallization of metal melts is very problematic. To solve theoretical problems, it must be considered that the crystallization of metal melts is mainly an equilibrium process in which nanocrystals play a major role.